The Role of Bhabinkamtibmas Through Counseling Activities in Preventing Drug Abuse in the Legal Area of the Tanah Karo Police - Steven Daniel Ginting (Advances in Police Science Research Journal, 2021)
The background of the research was appointed based on security issues, especially drug abuse which is increasing in the jurisdiction of the Tanah Karo Police. The purpose of the study was to determine the role of Bhabinkamtibmas in carrying out counseling to prevent drug abuse in the jurisdiction of the Tanah Karo Police and the factors that influence it. This research uses management theory proposed by George R. Terry and Communication Theory, prevention concept and Bhabinkamtibmas which support this research. This research was conducted with a qualitative approach and using evaluative research. The data sources of this research are primary and secondary sources. Data collection techniques were carried out by interview, observation and documentation. The results of the research on the role of Bhabinkamtibmas in carrying out counseling to prevent drug abuse in the jurisdiction of the Tanah Karo Police based on management theory by George R Terry, namely in planning, organizing, implementing and controlling as well as management elements such as man, machine, materials, money, method and market. still not implemented according to theory. This is influenced by external and internal factors. Internal factors include human resources, facilities and infrastructure and budget, while external factors are influenced by community culture and support from other parties. From the research findings, the authors write suggestions as follows: 1) Improve the quality and competence of Bhabinkamtibmas; 2) Cooperating with parties outside the National Police and maximizing resources. 3) Increase the number of personnel within the Tanah Karo Police Station; 4) Utilize technology to support tasks.